Postpartum unscarred uterine rupture caused by placenta accreta: A case report and literature review. Issue 3 (24th January 2021) - Okaniwa, Jun; Higeta, Daisuke; Kameda, Takashi; Uchiyama, Yosuke; Inoue, Maki; Iwase, Akira
Key Clinical Message: Our case and the literature review suggest that placenta accreta spectrum, with use of uterotonics and manual removal of placenta, could be risk factors for postpartum unscarred uterine rupture. Abstract : Our case and the literature review suggest that placenta accreta spectrum, with use of uterotonics and manual removal of placenta, could be risk factors for postpartum unscarred uterine rupture.